Electrochemical Characterization of Al 1100 Alloy in Different Concentration of Ammonium Chloride Solution at Laboratory Temperature. - Pruthviraj, R. D.; Vishwa, Prakash (Chem Sci J , Vol 8(4), 2017)
In this study of Al 1100 alloy is selected, the corrosion test was conducted at room temp using Electrochemical studies. The corrodent medium used for the test was 1 M, 75 M, 0.5 M and 0.25 M Ammonium chloride solution. The specimen was washed with distilled water fallowed by acetone and allowed to dry thoroughly the corrodent specimen was cleaned with brush for remove adhering corrosion product washed with water and acetone, then dried. The corrosion rates are calculated using CH-Instrument. In each case the corrosion rate in ammonium chloride solution decreases and the corrosion becomes decrease in exposure time for Al alloy due to the aluminium in many induced passivation due to the formation of metal chloride layer.
Keywords: Al 1100 alloy; NH4Cl; Weight loss; Electrochemical studies; Impedance; XRD; SEM